Real-world analysis of treatment patterns, effectiveness, and safety of daratumumab-based regimens in Chinese patients with newly diagnosed or relapsed/refractory multiple myeloma - Luqun Wang; Wei Yang; Yafei Wang; Ting Niu; Rong Fu; Yuping Zhong; Wenbin Qian; Kaiyang Ding; Kai Sun; Hong Liu; Baijun Fang; Hui Liu; et al. (BMC Cancer)
Abstract Background Daratumumab is a human IgGκ monoclonal antibody targeting CD38 with direct on-tumor and immunomodulatory mechanisms of action. Daratumumab-based treatment is a standard of care for multiple myeloma (MM) based on data from randomized controlled trials. Real-world studies, such as that presented here from China, provide important data to complement randomized trials. Methods This ongoing observational study describes real-world treatment patterns and outcomes among patients with symptomatic, newly diagnosed or relapsed/refractory MM treated with daratumumab in China. Patients must have received ≤ 3 prior lines of MM therapy. Data were collected prospectively and/or retrospectively, depending on time of treatment initiation. The primary study objective was to describe treatment patterns and clinical outcomes, and the secondary objective was to assess the safety and tolerability of daratumumab treatment. Results As of the cutoff date (April 30, 2023) for this analysis, 212 patients had received ≥ 1 dose of daratumumab at 13 sites in China. Regimens included daratumumab monotherapy (n = 22) and daratumumab combined with dexamethasone only (n = 21), proteasome inhibitors (PIs) ± dexamethasone (n = 57), immunomodulatory drugs (IMiDs) ± dexamethasone (n = 72), PIs and IMiDs ± dexamethasone (n = 29), and other combinations (n = 11). Daratumumab was initiated by 16.5%, 53.3%, 16.5%, and 13.7% of patients across the first, second, third, and fourth lines of therapy, respectively. A best overall response of partial response or better was achieved by 71.8% of evaluable patients and very good partial response or better was achieved by 51.4% of patients. Estimated 6-month and 12-month progression-free survival rates were 84.3% and 75.0%, respectively. Outcomes were generally more favorable with daratumumab-based combinations than with daratumumab monotherapy. Serious treatment-emergent adverse events were reported in 13.7% of patients, with pneumonia (4.7%) the only serious event in ≥ 5 patients. The most frequently reported adverse drug reactions were leukopenia (6.6%), neutropenia (5.7%), and thrombocytopenia (5.7%). Conclusions This observational study provides real-world insights into treatment decisions for Chinese patients with MM. The effectiveness and safety results support the use of daratumumab-based treatment as a standard-of-care therapy in Chinese patients with newly diagnosed or relapsed/refractory MM. This study is ongoing, with continued collection of outcomes data during a longer follow-up.